Consciousness and Science Fiction - Broderick, Damien (Science and Fiction,, 2018)
Science fiction explores the wonderful, baffling and wildly entertaining aspects of a universe unimaginably old and vast, and with a future even more immense. It reaches into that endless cosmos with the tools of rational investigation and storytelling. At the core of both science and science fiction is the engaged human mind--a consciousness that sees and feels and thinks and loves. But what is this mind, this aware and self-aware consciousness that seems unlike anything else we experience? What makes consciousness the Hard Problem of philosophy, still unsolved after millennia of probing? This book looks into the heart of this mystery - at the science and philosophy of consciousness and at many inspiring fictional examples - and finds strange, challenging answers. The book's content and entertaining style will appeal equally to science fiction enthusiasts and scholars, including cognitive and neuroscientists, as well as philosophers of mind. It is a refreshing romp through the science and science fiction of consciousness.